Brittany and the Angevins : province and empire, 1158-1203 - Everard, Judith, 1963- (Cambridge studies in medieval life and thought, 2000)
"The book examines in detail the means by which Henry II gained sovereignty over Brittany, and how it was governed subsequently by the Angevin kings of England from 1158 to 1203. In particular, it examines the extent to which the Angevins ruled Brittany directly, or delegated authority either to native dukes or royal ministers, and shows that in this respect the nature of Angevin rule changed and evolved over the period."--Jacket